PENGARUH E-WOM, KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE GLAD2GLOW DI TIKTOKSHOP - Nurul Zakina; Nur Elfi Husda (SCIENTIA JOURNAL, 2025)
This study aims to examine the extent to which E-WOM, product quality, and brand image influence the purchase decisions of Glad2Glow skincare products on TikTok Shop. The research population consists of individuals who follow or watch live broadcasts from the Glad2Glow TikTok Shop account, although the exact number is unknown. The sample was determined using the Lemeshow formula, resulting in 101 respondents, selected through non-probability sampling, specifically purposive sampling. Data collection was conducted through the distribution of questionnaires and analyzed using several data quality tests, including validity testing, reliability testing, and classical assumption tests (normality, multicollinearity, and heteroscedasticity tests). To assess the influence among variables, multiple linear regression analysis and the coefficient of determination (R²) were used. t-tests were conducted to evaluate the partial effects of each independent variable.The results of the study indicate that E-WOM, product quality, and brand image each have a significant partial influenceon consumers’ purchase decisions of Glad2Glow products on TikTok Shop.